Characterisation of thickness changes in the peripapillary retinal nerve fibre layer in patients with Leber's hereditary optic neuropathy. Issue 8 (29th August 2020) - Wang, Dan; Liu, Hong-Li; Du, Yang-Yang; Yuan, Jiajia; Li, Xin; Tian, Zhen; Zhou, Haiqiang; Wang, Shuang; Song, Lin; Sun, Jian; Xiao, Xiao; Wang, Zhi-Tao; et al.
Abstract : Background: Limited studies have identified the changes in peripapillary retinal nerve fibre layer (pRNFL) thickness in patients with chronic Leber's hereditary optic neuropathy (LHON) at different stages of the disease. We aimed to characterise the pRNFL thickness changes in patients with LHON having m.11778G>A ( MT-ND4 ) mutation. Methods: This retrospective cross-sectional study included 221 eyes from patients with LHON (n=145)—classified into seven groups according to disease duration—and 52 eyes from healthy controls (n=26). All subjects underwent pRNFL examinations. pRNFL thickness of the superior, nasal and inferior, and temporal quadrants, and the 360° average were measured. Results: Within 3 months of onset, the temporal pRNFL thickness decreased significantly, whereas the remaining quadrants and the average pRNFL thickness initially increased. The temporal quadrant (p<0.01) and average pRNFL thickness (p=0.02) significantly decreased at 3–6 months. Excluding that in the nasal quadrant (p=0.93), pRNFL thickness significantly decreased in all other quadrants at 6–9 months. At 9–12 months, the average and individual quadrant pRNFL thicknesses continued to decrease. Compared with 12–24 months, the pRNFL thickness was thinner at 24–60 months and >60 months. Conclusions: The papillomacular bundle was affected first and preferentially in LHON. pRNFL thickness initially increased and then decreased, corresponding to the retinal ganglion cell swelling and apoptosis. pRNFL thinning first occurred in the temporal quadrant, followed by the inferior and superior quadrants, and finally, the nasal quadrant. pRNFL continued to thin slowly in some quadrants even after 60 months.